The Effect of Inflation, Exchange Rate, Bi rate, Dow Jones Index on the Composite Stock Price Index (Empirical Studies on the Indonesian Stock Exchange in 2018-2022) - Inzira Fauzia NoviaSari; Hesti Setiorini; Yusmaniarti Yusmaniarti; Chairul Suhendra (Penerbit Jurnal Indonesia, 2023)
The Composite Stock Price Index (IHSG) is a reflection of the Indonesian economy, when the JCI shows an increase, it means that the Indonesian economy is in a conducive condition and vice versa. To be able to find out what can help the movement of the JCI, several factors need to be considered, such as inflation, the exchange rate, the BI rate and the Dow Jones index. The purpose of this study was to determine the effect of inflation, exchange rates, the BI rate and the Dow Jones index (DJIA) on the JCI. This research was conducted at the IDX using a sample of 60 consisting of monthly data for all variables from 2018 to 2022 by determining the sample using a saturated sample or census sample. The data analysis technique used was the Classical Assumption Test and Partial Hypothesis Test (T Test) and Simultaneous (F Test) with the help of the SPSS 22 Program. The results showed that partially Inflation (X1) had no effect on the JCI with a significant value of 0.358> 0 .05 and t count 0.927<2.004, Exchange Rate (X2) has no effect on JCI with a significant value of 0.389>0.05 and t count -0.869<2.004, BI Rate (X3) has no effect on JCI with a significant value of 0.242>0, 05 and t count -1.182 <2.004, the Dow Jones Index (X4) has an effect on the JCI with a significant value of 0.000 <0.05 and t count 4.962>2.004. While simultaneously Inflation, Exchange Rate, BI Rate, and the Dow Jones Index have a joint effect on the JCI with a sig value of 0.000<0.0.